Smart Make an Autonomous "Follow Me" Cooler - Oripov Shoxruxmirzo Muzaffarbek ugli (Peerian Journals Publishing, 2022)
In this project, we use an Arduino Uno to build an autonomous "follow me" cooler. The robot cooler connects to a smartphone via Bluetooth and uses GPS to navigate. All the electronics will be contained in the base so that other objects can be carried as well.
Keywords: Follow Me; MDF; HMC6883L; MG996R